An experimental analysis of the effects of d-amphetamine and cocaine on the acquisition and performance of response chains in monkeys. - Thompson, D M (1979)
In one component of a multiple schedule of food presentation, monkeys acquired a different four-response chain each session by responding sequentially on three keys in the presence of four geometric forms (learning). In the other component, the four-response chain was the same each session (performance). Both d-amphetamine and cocaine, at the higher doses, disrupted the behavior in the learning component; the overall response rate decreased, the overall accuracy was impaired (i.e., percent errors increased), and there was less within-session error reduction. The performance component was generally less sensitive than the learning component to the disruptive effects of both drugs on rate and accuracy. After pre-feeding or during an extended session, the response rate decreased in both components, but accuracy was generally unaffected. When the four discriminative stimuli in both components were removed, the behavior was disrupted to a greater extent in the performance component. The disruptive effects of both drugs on behavior in the learning component were attenuated when the drugs were administered during the session after the response chain had been acquired. It was concluded that the greater sensitivity of the learning component to disruptive drug effects is related to the relatively weak stimulus control and/or the lower rate of reinforcement associated with that component.